Road Accident Analysis - et. al., Dr. Anitha Patil, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
India being a highly populated country, the number of people using vehicles for commuting everyday is also high. With this there are a lot of accidents that takes place everyday. These accidents tend to effect a family very adversely with risk of lives or to endure the expense after it happens. This paper is to try and figure out ways to find accident prone regions and warn daily commuters regarding the accidents happening in that particular area. Accidents are something that happen without any prior intimation, but if we being a user of this interface we can be more careful when it comes to areas where accidents happen majorly. The user interface will notify a user regarding the accident prone regions being high medium and low. We will be using different algorithms in Machine learning to process the data to train and test a model. We are using data from a couple of years regarding accidents as datasets to divide them into these specific areas. This paper of ours follows the saying "It's better safe than sorry", and we see to help the users to avoid any accident that they might face